Lithuania - Country Economic Memorandum : Converging to Europe - Policies to Support Employment and Productivity Growth - World Bank (Washington, DC, 2013)
Lithuania's long-term economic strategy aims at building the foundations for achieving rapid convergence with Western European countries. The medium-term objective of the economic policy is to meet the economic criteria for accession and to get ready for membership in the European and Monetary Union (EMU) after accession. This will be acheived through continued macroeconomic stability, fiscal consolidation, and further implementation of structural reforms needed for an efficient functioning of the market economy, improved productivity, and enhancement of competitiveness. This report focuses on three critical elements of the structural reform agenda: 1) labor market reform, aimed at increasing labor market flexibility and improving the utilization of labor resources throughout the economy; 2) regulatory reform and reform of the business environment, to support private sector development and growth in both urban and rural areas; and 3) social protection reform, to improve targeting, effectiveness, and efficiency.